Contralateral sensorineural deafness in the absence of temporal bone fractures: an ignored entity in traumatic brain injury - Stephen, Marie Christy Sharafine; Venugopalan, Anju; Thimmasettaiah, Nagaraj Bangalore (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Traumatic brain injury (TBI) associated with temporal bone fractures causing ipsilateral hearing loss is not uncommon. But contralateral sensorineural hearing loss (SNHL) in the absence of temporal bone fractures is not frequently encountered or looked for in TBI patients. A simple bed side tuning fork test followed by a formal audiogram underscore the importance of pre-emptive assessment to prevent a permanent handicap. We report a case of a young man with no prior ear disease or comorbidities, who sustained traumatic brain injury with right parieto-temporal hemorrhagic contusion and cervical myelopathy following a two-wheeler fall. Although, there was no evidence of temporal bone fractures, he developed sudden profound deafness on the contralateral side of the brain injury. Evaluation and treatment for the same were initially delayed as the management solely focused on his neurological complaints and as the hearing loss was contralateral it was perceived to be unrelated to his brain injury. We want to highlight the importance of thorough evaluation and screening for bilateral hearing loss in patients with TBI irrespective of the presence or absence of temporal bone fractures to initiate appropriate management. We also want to add our patient to the very few such cases reported in the literature. We analyzed these cases and reviewed the possible pathophysiological mechanisms behind this entity.